2011
DOI: 10.3109/17435390.2011.626532
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticle enhanced silver ion stress response inEscherichia coliK12

Abstract: This study investigated the dissolution-based toxicity mechanism for silver nanoparticles to Escherichia coli K12. The silver nanoparticles, synthesised in the vapour phase, are effective anti-bacterial agents against the Gram-negative bacterium, E. coli K12. The nanoparticles associate with the bacterial cell wall, appearing to interact with the outer and inner membranes, and then dissolve to release Ag(+) into the cell and affect a transcriptional response. The dissolution of these nanoparticles in a modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
145
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(151 citation statements)
references
References 58 publications
1
145
0
5
Order By: Relevance
“…Thus, despite having in vitro antimicrobial properties (Morrill et al, 2013, McQuillan et al, 2012, McQuillan and Shaw, 2014, Ivask et al, 2014), ingested AgNPs do not appear to have a similar effect on the gut microbiome as do broad-spectrum antibiotics (Theriot et al, 2014, Theriot et al, 2011, Bassis et al, 2014). This finding is significant in assessing the potential for antimicrobial effects of ingested silver nanoparticles at exposure levels likely to be encountered in consumer products and dietary additives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, despite having in vitro antimicrobial properties (Morrill et al, 2013, McQuillan et al, 2012, McQuillan and Shaw, 2014, Ivask et al, 2014), ingested AgNPs do not appear to have a similar effect on the gut microbiome as do broad-spectrum antibiotics (Theriot et al, 2014, Theriot et al, 2011, Bassis et al, 2014). This finding is significant in assessing the potential for antimicrobial effects of ingested silver nanoparticles at exposure levels likely to be encountered in consumer products and dietary additives.…”
Section: Discussionmentioning
confidence: 99%
“…Most in vitro experimental evidence suggests that dissolution and local silver ion concentration play a significant role in the antimicrobial activity of AgNP (McQuillan et al, 2012, McQuillan and Shaw, 2014, Behra et al, 2013), although some aspects are not entirely explained by Ag ion availability (McQuillan and Shaw, 2014, Ivask et al, 2014). Assuming that antimicrobial effects of silver are dependent on direct interaction with gut microbes (Volker et al, 2013, Behra et al, 2013), particles present in higher luminal concentrations in the distal gut, which is the site of maximal bacterial concentration, may be more likely to have antimicrobial effects.…”
Section: Discussionmentioning
confidence: 99%
“…It results in great uncertainty when exploring the mechanisms underlying the microbial toxicity of NPs. For example, numerous studies have found that solvated Ag ĂŸ from silver NPs (Ag NPs) into the soluble phase during toxicity assays were too low to explain the observed antibacterial effects (Gunawan et al, 2009;Jin et al, 2010;McQuillan et al, 2012;Sotiriou and Pratsinis, 2010). However, Wang et al (2013) found it possible to underestimate the Ag ĂŸ releasing during exposure, making it difficult to discern whether Ag NPs exerted particlespecific toxicity.…”
Section: The Ion-related Toxicitymentioning
confidence: 96%
“…Antibiotics can have adverse effects on intestinal health by eliminating normal intestinal microbes (Antonopoulos et al, 2009). Silver is known to have antimicrobial properties (McQuillan et al, 2012; Morrill et al, 2013). It is unknown whether concurrent AgNP ingestion will enhance antimicrobial effects of a typically well-tolerated antibiotic dose, causing potential adverse effects due to disruption of normal gastrointestinal microbes (e.g.…”
Section: Introductionmentioning
confidence: 99%